2019
DOI: 10.1016/j.stem.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Human Spermatogonial Stem Cells Scrutinized under the Single-Cell Magnifying Glass

Abstract: Summary Spermatogonial stem cells (SSCs) are essential for adult spermatogenesis. Recently, Wang et al. (2018), Guo et al. (2018), and Hermann et al. (2018) used single-cell RNA sequencing to define and molecular characterize human testicular cell populations, including spermatogonial subsets with characteristics of human SSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…The direct functional implications of this heterogeneity are beyond the scope of the present study, but may indicate there are differential roles for individual SNAIs in the 3‐10 clusters of SSC subpopulations, as defined by some of the studies above (reviewed in ref. 61). The tight regulation of SNAI transcription factors in spermatogenesis is an ongoing area of interest for our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The direct functional implications of this heterogeneity are beyond the scope of the present study, but may indicate there are differential roles for individual SNAIs in the 3‐10 clusters of SSC subpopulations, as defined by some of the studies above (reviewed in ref. 61). The tight regulation of SNAI transcription factors in spermatogenesis is an ongoing area of interest for our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous production of a large number of sperm depends on the self‐renewal and differentiation of SSCs (Suzuki & Withers, 1978; K. Tan & Wilkinson, 2019). To ensure the stability of normal physiological processes of spermatogenesis, a large number of transcription factors are needed to regulate the dynamic balance of self‐renewal and differentiation of SSCs (K. Tan & Wilkinson, 2019). For the low expression of well‐known self‐renewal maintaining transcription factors, we concluded that CD49f − cells were differentiated spermatogonia cells.…”
Section: Discussionmentioning
confidence: 99%
“…They are also known as male germline stem cells (mGSCs), which are capable of differentiating into a series of spermatocytes and sperm cells (Phillips, Gassei, & Orwig, 2010). Scientists have been using a variety of tools and methods to explore gametogenesis and germline‐niche communication (K. Tan & Wilkinson, 2019). Large amounts of progressions on mice and human SSCs study were obtained through a wide variety of approaches (Garbuzov et al, 2018; Kaomei et al, 2006; Kubota, Avarbock, & Brinster, 2004; Law & Oatley, 2020; Legrand et al, 2019; L. Li et al, 2017; N. Li et al, 2019; Park et al, 2019; Pech et al, 2015; Sohni et al, 2019a; K. Tan & Wilkinson, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single cell RNA sequencing and bioinformatic analyses have revealed four type of undifferentiated spermatogonia in adult testis and three germ cell subsets in neonatal testis. UCHL1, PLZF and LIN28 are expressed both undifferentiated and differentiated spermatogonia (Sohni et al, 2019; Tan and Wilkinson, 2019). Because these transcripts are not specific for any subpopulation of undifferentiated spermatogonia, it is not possible to determine which subtype of spermatogonia is proliferating in vitro .…”
Section: Discussionmentioning
confidence: 99%